APPLICATION OF PROGRAM-TARGET APPROACH TO MANAGING THE EDUCATION OF YOUNG RUSSIAN GENERATION - R. Gavva (Вестник университета)
Domestic and world experience in managing the economy and the social sphere confirms the applicability of targeted programs to the solution of the problems of the development of education and the improvement of educational work with youth. The experience of developing and implementing federal targeted and state programs for the development of education in the Russian Federation in terms of their performance of the functions of educating children, adolescents, and young people has been article analyzed. The need for a more complete reflection of educational principles in educational programs is shown, for which purpose it is necessary to single out the category of targeted programs for managing the education of decent behavior of young people.